Effect of milk-replacer vs ewe milk rearing on vitamin E content of suckling lamb meat - Osorio M.T.; Zumalacárregui J.M.; Mateo J. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Ten carcasses from suckling lambs of the Churra breed hand reared with milk substitute and ten carcasses from lambs reared with ewe milk were studied in order to evaluate the effect of the type of rearing on the content of vitamin E in the m. longissimus dorsi of suckling lamb. For analysis of vitamin E, the fat from m. longissimus dorsi was extracted and HPLC analyses were carried out. a-, ?- and d- tocopherols were detected. Substantial differences in vitamin E levels in intramuscular fat from lambs of the two treatments were observed. Fat of lambs reared exclusively with milk substitute showed a higher content of a- and ?-tocopherols (P<0.05 and P<0.001, respectively) than the fat from breast-reared lambs. This study showed that vitamin E content in the meat of suckling lambs is influenced by the type of feeding.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)